Neutralising ordnance with non-extending elements - Golodyaev, Alexander I. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The method of neutralising ordnance by rinsing explosive materials with a solution enables significant cost saving while reducing the risk pyrotechnic personnel is exposed to, especially during ammunition transport to recycling sites. Costs for necessary special equipment are minimal. The technology is easy to be automated using an electronic and remotely controlled drilling process which reduces the risk of explosion to the minimum. This demining method will prove effective especially for operations against guerrilla mine warfare.